2022
DOI: 10.3390/biom12101424
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Deubiquitinating Enzymes in Human and Plant Pathogenic Fungi

Abstract: In eukaryotic cells, a large number of proteins are modified by ubiquitination, which leads to proteasomal degradation or change in protein function. The protein ubiquitination process can be reversed by a process called deubiquitination, which plays an important regulatory mechanism in cellular control. Deubiquitination is catalyzed by deubiquitinating enzymes (DUBs); the cysteine proteases specifically cleave off ubiquitin from ubiquitinated substrates or ubiquitin precursors. Over the past two decades, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…48 In addition to WD40 domain, Doa1 contains PFU and PUL domains, 25 whereas Doa4 consists of DUSP and UCH domains. 29 However, the precise role of each domain in phytopathogenic fungi remains unclear. Our results demonstrate that all conserved domains of FonDoa1 are essential for its function in the Fon infection process, as different domains of Doa1 could not independently restore the pathogenicity defect (Figure 5).…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…48 In addition to WD40 domain, Doa1 contains PFU and PUL domains, 25 whereas Doa4 consists of DUSP and UCH domains. 29 However, the precise role of each domain in phytopathogenic fungi remains unclear. Our results demonstrate that all conserved domains of FonDoa1 are essential for its function in the Fon infection process, as different domains of Doa1 could not independently restore the pathogenicity defect (Figure 5).…”
Section: ■ Discussionmentioning
confidence: 99%
“…The WD-repeat domain of Doa1 has been shown to regulate diverse cellular functions, such as regulation of signal transduction, transcription, pre-mRNA processing, or cell structure maintenance . In addition to WD40 domain, Doa1 contains PFU and PUL domains, whereas Doa4 consists of DUSP and UCH domains . However, the precise role of each domain in phytopathogenic fungi remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that in Saccharomyces cerevisiae , Dubs are crucial for various biological processes such as stress response, pre‐mRNA editing, protein sorting, and transport (Hutchins et al ., 2013). Beyond yeast, the role of deubiquitinating enzymes in pathogenic fungi has also been documented (Wang et al ., 2022). For instance, the deubiquitinating enzyme Ubp3 influences appressorium formation and maturation by targeting the GTPase‐activating protein Smo1 for deubiquitination in Magnaporthe oryzae (Cai et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%